Role of chemical exposure in induction and evolution of vitiligo: a retrospective cross-sectional study from tertiary care center, North India - Tanreet Kaur; Tejinder Kaur; Jaspreet Kaur (Wolters Kluwer Medknow Publications, 2023)
Background: Vitiligo in general is a disease of multiple hypotheses. Some forms of vitiligo vulgaris are in fact caused by household/occupational exposure to certain chemicals which may simply accelerate oxidative stress pathways in melanocytes resulting in their destruction in genetically predisposed individuals. Aims: The basic objectives of this retrospective cohort study were to determine the role of chemical exposure in induction and evolution of vitiligo, to find any association between the duration of chemical exposure and the duration of the disease and to observe the outcome of the disease upon avoidance of suspected chemicals. Methods: In this retrospective study, the records of 81 patients with vitiligo at Government Medical College, Amritsar were evaluated. The primary data were obtained from the performa containing elaborative details regarding demographic and clinical profile of the patients including type of chemical, site, and duration of chemical exposure. Statistical analysis to detect correlation coefficient (R-value) between duration of chemical exposure and duration of disease was performed using SPSS 22.0 version software. Outcome of the disease upon avoidance of chemicals was also documented. Results: In a total of 81 patients of vitiligo, 41.97% were employed in leather industry, 12.34% patients were laborer involved in cement work, 35.41% of females were exposed to household chemicals present in detergents, etc., and 27.7% of the males were farmer by occupation. Acrofacial pattern was observed in 56.79% patients followed by generalized type (29.62% patients). Only 28.39% patients reported symptoms such as pruritus, burning sensation, and erythema at the site of exposure. About 69.13% patients (n = 56) showed positive correlation between site of chemical exposure and site of onset of vitiligo. The mean duration of vitiligo was 6.20 ± 2.51 years and mean duration of chemical exposure was 11.20 ± 4.51 years. The duration of disease and duration of chemical exposure showed no correlation (R = +0.134 and P = 0.490). There was significant reduction in mean percentage of body surface area involved with vitiligo in fully compliant patients (P = 0.01) versus noncompliant patients (P = 0.07). Conclusion: It was observed that several chemical compounds, most of which containing phenol groups in their structure, have role in triggering vitiligo. Complete avoidance of exposure has definite role in haulting the progression of the disease. However, more prospective cohort studies are needed in future to determine the causality.